Familial ALS-associated SFPQ variants promote the formation of SFPQ cytoplasmic aggregates in primary neurons. Issue 9 (28th September 2022) - Widagdo, Jocelyn; Udagedara, Saumya; Bhembre, Nishita; Tan, Jing Zhi Anson; Neureiter, Lara; Huang, Jie; Anggono, Victor; Lee, Mihwa
Abstract : Abstract : Splicing factor proline- and glutamine-rich (SFPQ) is a nuclear RNA-binding protein that is involved in a wide range of physiological processes including neuronal development and homeostasis. However, the mislocalization and cytoplasmic aggregation of SFPQ are associated with the pathophysiology of amyotrophic lateral sclerosis (ALS). We have previously reported that zinc mediates SFPQ polymerization and promotes the formation of cytoplasmic aggregates in neurons. Here we characterize two familial ALS (fALS)-associated SFPQ variants, which cause amino acid substitutions in the proximity of the SFPQ zinc-coordinating centre (N533H and L534I). Both mutants display increased zinc-binding affinities, which can be explained by the presence of a second zinc-binding site revealed by the 1.83 Å crystal structure of the human SFPQ L534I mutant. Overexpression of these fALS-associated mutants significantly increases the number of SFPQ cytoplasmic aggregates in primary neurons. Although they do not affect the density of dendritic spines, the presence of SFPQ cytoplasmic aggregates causes a marked reduction in the levels of the GluA1, but not the GluA2 subunit of AMPA-type glutamate receptors on the neuronal surface. Taken together, our data demonstrate that fALS-associated mutations enhance the propensity of SFPQ to bind zinc and form aggregates, leading to the dysregulation of AMPA receptor subunit composition, which may contribute to neuronal dysfunction in ALS.